Determinar la asociación entre el modelo facial de Capelozza y maloclusiones según Angle en estudiantes de Bachillerato de la Unidad Educativa Nambacola - Cullquipuma Gutiérrez, Marco Israel (2019)
Properly diagnosing of malocclusion has been the most important issue in orthodontics. Therefore, this research aim is to "Determine the association between Facial Models according to Capelozza and Angle Malocclusions in teenagers patients at Unidad Educativa Nambacola " The present study is descriptive, cross-sectional and observational, it was carried out in Nambacola parish in the High School belonging to it, being the study universe of 93 students, of which by inclusion and exclusion criteria It was possible to delimit 57 participants (29 women and 28 men) as sample, who were taken 3 extra oral photos (frontal, profile and smile) and 5 intraoral photos (frontal, upper and lower occlusal, lateral right and left), in addition to the study models with bite registration, the analysis was subsequently carried out taking into account the parameters indicated by Capelozza and Angle to obtain an accurate diagnosis. The results obtained through the research reflects data with a higher prevalence of model 1 with 47.40%, followed by model 2 with 45.60%, model 3 with 5.30%, short face model with 1.80%; no participants were found with long face facial model. As regards malocclusions, a higher prevalence is established in Class I (54.40%), followed by Class II-2 (19.30%), Class III (14%) and Class II-1 (12.30%). According to sex, a higher proportion of female participants is established (50.90%); In relation to age, the group with the greatest predominance is in the 16 year old (28.10%). It can be concluded that there is no association between the Facial Model and Malocclusion, the greatest association was found between Model 2 and Class II-1 malocclusion. Key Words: maloclusion, facial pattern , prevalence.